Agglomeration during spray drying: Physical and rehydration properties of whole milk/sugar mixture powders. (15th September 2017) - Chever, S.; Méjean, S.; Dolivet, A.; Mei, F.; Den Boer, C.M.; Le Barzic, G.; Jeantet, R.; Schuck, P.
Abstract: In general, milk powders are submitted to agglomeration in order to enhance their rehydration properties. This study evaluated the impact of six different methods of agglomeration of the same sweet whole milk powder on the physical and rehydration properties of the final product: non-agglomerated powder (control); agglomerated powder with fines returned to the top of the dryer, above the internal fluid bed (IFB) or above the cone; and agglomerated powder with fines returned above the IFB with a nozzle that injects steam or sprays water in the middle of the IFB, respectively. As expected, the biochemistry results showed no difference since the same concentrate was used in the whole set of experiments. The physical properties led to higher bulk densities, tapped densities and interstitial air for the control, and higher occluded air and particle size for agglomerated powders, regardless of the agglomeration process. All of these physical properties influenced the rehydratability. In fact, the wetting time and the dispersibility of sweet whole milk powder were significantly improved by the agglomeration method, with the return of fines and steam injection in the IFB. An experimental design of the agglomeration process was devised for this agglomeration approach. Highlights: Various agglomeration steps to rehydrate sweet milk powders were studied. The rehydration properties depended on the configuration of the dryer. The optimal scheme consisted of steam injection in the internal fluidized bed.